Solomon Islands : Disaster Risk Financing and Insurance - World Bank (Washington, DC, 2015)
This report aims to build understanding of the existing disaster risk financing and insurance (DRFI) tools in use in the Solomon Islands and to identify gaps where engagement could further develop financial resilience. It also aims to encourage peer exchange of regional knowledge, specifically by encouraging dialogue on past experiences, lessons learned, optimal use of these financial tools, and the effect these tools may have on the execution of post-disaster funds. The Solomon Islands is located in an area known for frequent tropical cyclones and is also in the Pacific Ring of Fire, an active seismic area. Consequently, it is exposed to both hydrometeorological and geophysical hazards. This exposure was clearly demonstrated at the end of December 2012, when the country experience Tropical Cyclone Freda, followed in early February 2013 by a magnitude 8.0 earthquake and a subsequent tsunami affecting the Santa Cruz Islands. The Solomon Islands is expected to incur, over the long term, average annual losses of SI$145 million (US$20 million) due to earthquakes or tropical cyclones. In the next 50 years, the Solomon Islands has a 50 percent chance of experiencing a single event loss exceeding SI$1.7 billion (US$240 million), and a 10 percent chance of experiencing a single event loss exceeding SI$3.7 billion (US$520 million) (PCRAFI 2011).